Update of the COVID-19 Higher Education Literature Database (CHELD v2) (Journal of Applied Learning and Teaching, 2021)
The COVID-19 Higher Education Literature Database (CHELD) was created in 2020 to assist researchers with the publication of systematic literature reviews by completing the first step in a systematic literature review for them. Initially containing the first six months of literature related to COVID-19 and teaching and learning in higher education, this short communication presents the updated database. The CHELD Version 2 contains all identified journal articles published between 1 January and 31 December 2020 using a systematic literature review method. The rigorous process of article selection provides researchers with a validated source of literature from which they can more rapidly draw meaningful conclusions about the impact of COVID-19 on higher education learning and teaching. Whilst initially created as a researcher tool, the CHELD v2 can also be used by university leaders to identify rapid response measures undertaken by other institutions, and by educators seeking to identify new innovations to support the quick transition to online or emergency teaching.